Collagen-Agarose Co-Gels as a Model for Collagen-Matrix Interaction in Soft Tissues Subjected to Indentation - Lake, Spencer P. (2011)
The mechanical properties of soft tissues depend on the collagen fiber network and the surrounding non-fibrillar matrix. The mechanical role of non-fibrillar material remains poorly understood. Our recent study (Lake and Barocas, 2011) introduced collagen-agarose co-gels as a simple experimental model system to evaluate the mechanical contribution of non-fibrillar matrix, and evaluated co-gel properties in uniaxial tension. In this study, we utilized similar co-gels to examine collagen-matrix interaction in tissues subjected to incremental stress-relaxation indentation tests. Mechanical testing was performed using two orthogonal custom test devices and polarized light imaging was used to quantify 3D collagen fiber kinematics under load. The addition of agarose led to concentration-dependent changes in the time-dependent mechanical response and magnitude/spread of collagen fiber reorganization of tissue analogs. Specifically, peak/relaxed loads increased, and relaxation rate decreased, with increasing agarose concentration. In addition, increasing agarose content led to larger magnitude changes in orientation direction and alignment strength that were more localized near the indenter. Results suggest that non-fibrillar material significantly contributes to the behavior of co-gels in indentation, likely by reducing permeability and resisting volume change, thereby providing insight into the properties of artificial and native tissues subjected to non-tensile loading.